A Formação do ]Arquivo[ da Coleção Amazoniana de Arte da Universidade Federal do Pará e a fotografia de Paula Sampaio como um fator de diálogo permanente entre os acervos - BARBOSA, Maria Christina Monteiro (2020)
The Amazonian Art Collection of the Federal University of Pará, conceived and organized by professor and researcher Orlando Maneschy brings together works in the sections Visual Arts and Fashion, and is an immersion in the Amazon region that goes beyond a set of art objects, which allows us to observe a project committed to the local reality that needs to be publicized in a way that society becomes a participant in the events. The ]Archive[which now conforms to this collection, establishes, through books, digital archives, newspapers and other printed matter, as well as audiovisual material, a dialogue with the works deposited in the collection, due to the rich material it possesses, much of it the result of academic or non-academic research, creating and showing subjective paths of the collection, such as the work produced by the photographer Paula Sampaio, who has been recording the Amazon for more than 20 years, and is a national reference in photographic documentation.